Gas sensing devices based on two-dimensional materials: a review - Wang, Boran; Gu, Yi; Chen, Lin; Ji, Li; Zhu, Hao; Sun, Qingqing (Nanotechnology, 2022)
Gas sensors have been widely utilized penetrating every aspect of our daily lives, such as medical industry, environmental safety testing, and the food industry. In recent years, two-dimensional (2D) materials have shown promising potential and prominent advantages in gas sensing technology, due to their unique physical and chemical properties. In addition, the ultra-high surface-to-volume ratio and surface activity of the 2D materials with atomic-level thickness enables enhanced absorption and sensitivity. Till now, different gas sensing techniques have been developed to further boost the performance of 2D materials-based gas sensors, such as various surface functionalization and Van der Waals heterojunction formation. In this article, a comprehensive review of advanced gas sensing devices is provided based on 2D materials, focusing on two sensing principles of charge-exchange and surface oxygen ion adsorption. Six types of typical gas sensor devices based on 2D materials are introduced with discussion of latest research progress and future perspectives.